ELISA kit for peanut protein determination: collaborative study - Lexmaulová, Hana; Gabrovská, Dana; Rysová, Jana; Stumr, Frantisek; Netusilová, Katerina; Blazková, Martina; Bulawová, Hana; Brychta, Josef; Subrtová, Zdenka; Pavelka, Jiri; Iametti, Stefania; Del Barco, Jorge Antonio Guisantes; et al. (Journal of AOAC International, 2013)
A collaborative study in 10 laboratories was performed to validate an ELISA method developed for the quantitative determination of peanut protein in foods. The ELISA kit used for this study is based on rabbit polyclonal antibody. This kit does not produce any false-positive results or cross-reactivity with a broad range of peanut-free food matrixes. All participants obtained the peanut ELISA kit with standard operational procedures, a list of samples, the samples, and a protocol for recording test results. The study included 15 food samples. Three food matrix samples of zero peanut content showed peanut protein content lower than the first standard (0.10 mg/kg). Three samples with peanut declared as an ingredient revealed peanut protein content outside the calibration curve (absorbance was above the highest standard) in all laboratories, and three samples had the peanut content reported either above the highest standard or within the calibration curve, depending on the laboratory. Six samples with peanut declared as an ingredient gave the peanut protein content within the calibration curve. Only these six samples, together with a positive control sample (CS2), were used for statistical evaluation. The statistical tests (Cochran, Grubbs, and Mandel) and analysis of variance were used for the evaluation of the collaborative study results. Repeatability and reproducibility limits, as well as an LOQ (LOQcollaborative 0.22 mg peanut proteins/kg) and an LOD (LODcollaborative 0.07 mg peanut proteinslkg) for the kit were calculated.
Keywords: Cooperative Behavior; rostlinné proteiny; Enzyme-Linked Immunosorbent Assay; Limit of Detection; Plant Proteins; kooperační chování; Arachis; limita detekce; ELISA; reagenční diagnostické soupravy; Reagent Kits, Diagnostic